Structure of seeds of succulent representatives of Apocynaceae family - Авєкін, Я. В.; Нужина, Н. В.; Гайдаржи, М. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
Anatomical and morphological investigations of seeds of four succulent representatives of the family Apocynaceae have been conducted. According to the research, it has been found that the structure of the seeds of P. lamerei, P. rutenbergianum, A. obesum and A. arabiсum is similar to other mesophytic representatives of the family Apocynaceae in shape, sculpture of the testa surface and endosperm type. Among the differences it has been found that the testa of studied species has exo-mesotestal type of structure, that is typical for representatives of the family Asclepiadaceae or, according to modern concepts, for subfamily Asclepiadoideae. It has been also found that embryos of the studied species have more developed thickened hypocotyl compared with mesophytic representatives of this family. Between the taxa A. obesum and A. arabicum, which are combined in one species A. obesum in the system APG III, there have been revealed a number of differences in the anatomical structure of the seeds. They differ in size, color, surface sculpture, thickness of testa and the type of structure of its epidermal cells, which may indicate their possible non-affinity.